Associations of physical activity and sedentary behaviors with child mental well-being during the COVID-19 pandemic - Amanda S. Gilbert; Laurel Schmidt; Alan Beck; Maura M. Kepper; Stephanie Mazzucca; Amy Eyler (BMC, 2021)
Abstract Background The COVID-19 pandemic resulted in public health and policy measures to reduce in-person contact and the transmission of the virus. These measures impacted daily life and mental well-being (MWB). The aims of this study were to explore the MWB impacts of COVID-19 on children and assess the associations among perceived changes in physical activity (PA) and sedentary behaviors (SB), with perceived MWB changes, using a mixed-methods approach. Methods A convergent parallel mixed-methods design consisting of an online survey with a convenience sample and interviews was conducted from May through July 2020 with parents/caregivers of kindergarten through 5th graders in the St. Louis region. Survey domains assessed included child MWB, PA, and SB. Interviews were recorded, transcribed, and qualitatively analyzed using a code book developed to elicit themes. Survey data was analyzed with chi-squared tests and logistic regressions. The dependent variable was perceived change in child MWB due to the impact of COVID-19. Independent variables included perceived changes in PA, SB, and child concerns about COVID-19. Results Sample size consisted of 144 surveys and 16 interviews. Most parents reported a perceived decrease in child MWB (74%), a decrease in child PA (61%), and an increase in child SB (91%). Discontentment with stay-at-home orders and concern about COVID-19 were associated with a perceived decrease in MWB. Children whose PA decreased were 53% less likely to have the same or better MWB (OR 0.47) and children whose outside PA decreased were 72% less likely to have the same or better MWB (OR 0.28). Common qualitative themes included difficulty in adjusting to COVID-19 restrictions due to school closures and lack of socializing, child concerns about family getting sick, and PA benefits for improving MWB. Conclusions Based on parent perceptions, MWB decreased with COVID-19. Maintained or increased child PA improved the chances MWB would remain the same or improve. Parent interviews provide context to these findings by showing how COVID-19 impacted MWB and the associations between PA and MWB. Understanding protective factors for child MWB during COVID-19 is important to offset negative long-term health outcomes from this ongoing pandemic.